IMPLEMENTATION OF RESTORATIVE APPROACH FOR MEDICAL DISPUTE RESOLUTION IN INDONESIA - Hotmaria Hertawaty Sijabat (Adisam Publisher, 2025)
The handling of medical disputes in Indonesia often results in prolonged conflict through litigation processes that drain the time, money and emotions of the parties involved. A more humane and constructive alternative is the implementation of a restorative approach that focuses on dialogue, rapprochement, and reaching a mutual agreement. This approach aims to create a win-win solution between patients, medical personnel, and healthcare institutions. This article discusses the potential and challenges of implementing restorative approaches in the context of medical dispute resolution in Indonesia. It is found that while this approach offers many benefits, such as reducing the burden on the judicial system and improving relationships between disputing parties, its implementation is hampered by the lack of specific regulations, lack of socialisation, and limited professional mediators. Support from the government, health institutions, and efforts to change the culture of litigation among the community are key to the success of implementing this approach. In conclusion, with the strengthening of regulations and training of mediators, the restorative approach has great potential to increase public trust in Indonesia's health system and provide a fairer and more dignified dispute resolution.